Understanding of Vector Materials with PAILKEM (Active, Innovative, Environmental, Creative, Effective, and Interesting Learning) - Radha Krisnamurti Sigamura (BRIDGE : The Multidisciplinary Research Portal, 2023)
There are many mathematics learning strategies used by educators to achieve more optimal results. The PAILKEM learning strategy is one of the learning strategies that makes it possible to achieve learning objectives. The purpose of this study is to improve comprehension results. The hypothesis in this study is that there is a significant influence of the PAILKEM learning strategy (Active, Innovative, Environmental, Creative, effective, and Interesting Learning) on understanding vector material. This research method uses an experimental method using a True Experimental Design. Data analysis was performed using the t-test. The results of the study, after testing the hypothesis using the t-test with a significant level of 0.05 and previously carrying out the normality test and homogeneity test, obtained tcount > ttable, namely tCount = 7.636> ttable = 1.6689, so that Ho was rejected and Ha was accepted. The conclusion in this study is that there is an influence of the PAILKEM learning strategy (Active, Innovative, Environmental, Creative, effective, and Interesting Learning) on the understanding of vector material.